Comparison of mechanical properties and color stability of various vacuum-formed orthodontic retainers: An in vitro study - Aljazi H. Aldweesh; Nassr S. Al-Maflehi; Muhannad AlGhizzi; Eman AlShayea; Sahar F. Albarakati (Saudi Dental Journal, 2023)
Background: Vacuum-formed retainer (VFR) is the most used retainer due to its higher aesthetic properties and lower cost, their mechanical properties of are important in determining the stability and long-term use of appliances made out of them. Aim: This study aimed to evaluate and compare the flexural modulus, surface hardness, and color stability of three different VFR materials. Methods: Three different VFR materials, namely Duran, Keystone, and Zendura, of 1 mm thickness, were tested after thermoforming for flexural modulus, hardness, and color stability. They were formed over a stainless-steel model of 12 mm diameter and 6 mm height. Results: There were significant statistical differences (p = 0.000) in the flexural modulus and hardness of the three materials. Regarding color stability, Zendura exhibited significantly higher ΔE* values than Keystone and Duran (p < 0.05). Conclusions: Zendura had the highest flexural modulus and hardness compared with Duran and Keystone; however, it is more susceptible to color change compared to the other tested materials.